Ghost nets: A poorly known threat to Brazilian freshwater biodiversity - AZEVEDO-SANTOS,VALTER M. (2022)
Abstract Ghost nets constitute a serious threat to aquatic biodiversity, because they entangle animals as long as they persist in the environment. However, scientific literature in Brazil is virtually silent about this issue in inland ecosystems. Concerned with this gap, we conducted searches on YouTube BR to gather information about ghost nets in Brazilian freshwaters. Through our search, we compiled 33 independent videos showing ghost nets in different aquatic environments. In several cases, we identified entangled animals (i.e., fishes, reptiles, and birds). In this work we also provide recommendations to better understand and mitigate this problem in Brazilian freshwater ecosystems.